2016
DOI: 10.1097/j.pain.0000000000000603
|View full text |Cite
|
Sign up to set email alerts
|

Pain sensitivity profiles in patients with advanced knee osteoarthritis

Abstract: The development of patient profiles to subgroup individuals on a variety of variables has gained attention as a potential means to better inform clinical decision-making. Patterns of pain sensitivity response specific to quantitative sensory testing (QST) modality have been demonstrated in healthy subjects. It has not been determined if these patterns persist in a knee osteoarthritis population. In a sample of 218 participants, 19 QST measures along with pain, psychological factors, self-reported function, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 60 publications
3
49
1
2
Order By: Relevance
“…Similarly, previous research has demonstrated increased generalized pressure pain sensitivity in patients with knee OA pain, suggesting the presence of central sensitization to mechanical stimuli (Arendt-Nielsen et al 2010; Frey-Law et al 2016). These lower functioning participants also exhibited greater heat and mechanical temporal summation.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similarly, previous research has demonstrated increased generalized pressure pain sensitivity in patients with knee OA pain, suggesting the presence of central sensitization to mechanical stimuli (Arendt-Nielsen et al 2010; Frey-Law et al 2016). These lower functioning participants also exhibited greater heat and mechanical temporal summation.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, movement-evoked pain is associated with sensitization of peripheral Aδ and C-fiber afferents (Brucini et al 1981; Hendiani et al 2003), while spontaneous pain or pain at rest is related to sensitization at the dorsal horn and spinal cord (Schaible et al, 2002). Also, increased heat temporal summation implicates centrally-mediated mechanisms, and evidence suggests that in some individuals, peripheral and central nervous system mechanisms significantly contribute to knee OA pain (Murphy et al 2011; Arendt-Nielsen et al 2010; Frey-Law et al 2016; Cardoso et al 2016). Future mechanism-based research is needed incorporating measures of temporal summation of movement-evoked pain and their associations with physical function and intervention outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there is substantial heterogeneity across individuals with fibromyalgia (FM) and chronic musculoskeletal pain conditions such as osteoarthritis (OA; e.g., [3, 52, 65, 142, 153]), with similar sensory heterogeneity also observed in patients with systemic inflammatory conditions such as rheumatoid arthritis [92]. Moreover, since no particular QST profile is unique to a given pain diagnosis (e.g., [63]), these “trans-etiological” patterns of sensory symptoms and deficits may reflect distinct pain mechanisms, and it may be possible to group together individuals with similar sensory profiles diagnosed with these conditions.…”
Section: Recommendationsmentioning
confidence: 99%
“…La osteoartrosis (OA) de rodilla es un desorden mecánico y dinámico multifactorial de la articulación, inducido por mediadores enzimáticos, que comprende diferentes fases y fenotipos, dando como resultado la pérdida del cartíla-go articular, esclerosis del hueso subcondral, formación de osteofitos y quistes subcondrales, que puede afectar a uno o más de los tres compartimentos articulares (1,2) y en donde el dolor es la característica clínica más importante, asocián-dose frecuentemente a un trastorno de sensibilización central y periférica (1,3,4), con cambios en los umbrales de dolor evidenciados por hiperalgesia mecánica y térmica (principalmente al frío) (5). Esta articulación es diartrodial, con un sistema biológico complejo en donde el cartílago articular, una estructura avascular y aneural, se encuentra funcional y anatómicamente entre dos estructuras altamente vascularizadas e inervadas como lo son la membrana sinovial y el hueso subcondral, ambos dotados de receptores de calor, quimiorreceptores y mecanorreceptores (1).…”
Section: Introductionunclassified